ANALISIS KERUSAKAN GERBONG DATAR "PPCW" 42 TON AKIBAT BEBAN OPERASI - ., Anwar; Gozali, M. (Jurnal Material Komponen dan Konstruksi, 2016)
Several units of PPCW wagons capacity of 42 ton are used for the cement transportation, cracked on the under frame structures. To determine the cause of the cracks, the investigation was conducted by measuring the stress that occurs when the wagons operation. Results of the investigations are the mean stresses and amplitude stresses measured in real-time in the various road conditions, and then be analyzed using fatigue limit diagram approach to get fatigue strength of the wagon structure. The analysis result shows that the stresses at several points of the wagon structure under the operational loads are in the critical area or is above the fatigue limit diagram. This is the cause of the failure of the under frame of the PPCW wagon structure. Abstrak Beberapa unit gerbong PPCW kapasitas 42 ton yang digunakan untuk pengangkutan semen, mengalami retak pada bagian rangka bawah. Untuk menegetahui penyebab terjadinya retak tersebut, dilakukan penelitian dengan cara mengukur tegangan yang terjadi pada saat gerbong beroperasi. Hasil penelitian berupa besaran tegangan rata-rata dan tegangan amplitudo yang diukur secara real-time pada berbagai kondisi jalan, dianalisis dengan menggunakan pendekatan diagram batas lelah. Hasil analisis menunjukkan bahwa tegangan pada beberapa titik berada pada daerah kritis atau diagram garis batas lelah. Hal ini merupakan penyebab terjadinya kerusakan struktur rangka bawah gerbong PPCW. Keywords : PPCW wagon, stresses, fatigue limit diagram.